NANOENCAPSULATION OF ETHANOL EXTRACT OF PAPAYA LEAF (CARICA PAPAYA LINN.) USING CHITOSAN AND TESTING ITS EFFECTIVENESS AS AN ANTI-INFLAMMATORY - ANDRIE, MOHAMAD; TAURINA, WINTARI (International Journal of Applied Pharmaceutics, 2024)
Objective: Papaya is a plant typical of West Kalimantan which has many properties such as anti-inflammatory, analgesic, antimalarial, and antibacterial. This research aims to formulate ethanol extract of papaya leaves into a nanoencapsulated preparation and test its effectiveness as an anti-inflammatory. Methods: Nanoparticle formulations made with the ionic gelation method use polymer chitosan (0.25%-1%) with crosslinker sodium tripolyphosphate (0.25%). Nanoencapsulation ethanol extract of papaya leaf was evaluated for characteristics including particle size distribution, index polydispersity, zeta potential, particle morphology, and entrapment efficiency. Furthermore, The efficacy of anti-inflammatory nanoencapsulation was then evaluated on male Wistar rats with carrageenan-induced inflammation using doses of 100 mg/kg and 200 mg/kg. The assessment of anti-inflammatory activity utilized the Rat hind paw edema method by observing the development of inflammation in the volume of the soles of the test animals' paws. Results: The results of nanoencapsulation characterization showed that papaya ethanol extract in Formula 1 with a ratio of Chitosan: Papaya Leaf Extract Ethanol: NaTPP = 6:1:1 was the best formula, exhibiting an average particle size of 217.3±47.8 nm, a polydispersity index value of 0.271, a zeta potential value of+34.3 mV, an entrapment efficiency value of 65.54, and a particle morphology that is less spherical. The test for anti-inflammatory activity of papaya leaf ethanol extract nanoparticles, administered orally at a dosage of 200 mg/kgBW, demonstrated the highest percentage of anti-inflammatory efficacy at 61.538%. In comparison, the positive control group (diclofenac sodium) exhibited 54.325%, and the low-dose group (100 mg/kgBW) showed 51.585%. The results showed that the ethanol extract of papaya, when nanoencapsulated in chitosan nanoparticles, exhibits good characteristics and has significant potential for inhibiting inflammation in male Wistar rats induced by carrageenan. Conclusion: The characterization results of the optimal chitosan-ethanol papaya leaf extract nanoparticles were obtained using Formula 1. Nanoparticles of chitosan-ethanol extract from papaya leaves at doses I and II exhibited anti-inflammatory activity that was not significantly different.